Electrodermal response to olfactory stimuli in children with autism spectrum disorder: a systematic review of emotional and cognitive regulation - David Pérez-Jorge; Elena Olmos-Raya; Isabel Alonso-Rodríguez; Itahisa Pérez-Pérez (Frontiers in Education)
IntroductionThe study of electrodermal activity (EDA) in individuals with Autism Spectrum Disorder (ASD) is gaining scientific interest as a potential source of physiological biomarkers that can objectively improve the diagnosis of this condition. Despite significant research into responses to visual and auditory stimuli, the response to olfactory stimuli has not been extensively explored.MethodsThis research involved a systematic literature review of studies on EDA responses to olfactory stimuli in ASD populations, published between 2000 and 2024. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure a rigorous and transparent methodology. From the selected scientific databases, such as Scopus and Web of Science, 20 publications met the inclusion and exclusion criteria for detailed analysis.ResultsThe analysis revealed that individuals with ASD display distinct electrodermal patterns compared to the typically developing population, especially in response to intense and emotionally evocative odors, which elicited the highest electrodermal reactivity.DiscussionThe pronounced electrodermal response to specific odors suggests that EDA could serve as a reliable physiological measure for predicting emotional states in individuals with ASD. This capability provides educators with valuable insights, allowing them to tailor educational strategies to the unique emotional needs of each moment, thereby optimizing the teaching and learning process.